Síndrome Nefrótico en el lactante mayor - Maldonado Leiva, Erika Maricel (2018)
The nephrotic syndrome is characterized by alteration of the capillary permeability of glomerular predisposing to the formation of edema, proteinuria results >50 mg/kg/dl or 40 mg/m2/hour, low serum albumin, albumin < 2.5 g/dl, hypercholesterolemia. (3). Estimated annual nephrotic syndrome incidence is 1 - 3 per 100,000 children under 16 years of age and occurs more frequently between 2 and 10 years. (1), being the male greater predominance. (2) , although there are no exact figures for the incidence of this disease in pediatric age group, in Ecuador the Pediatric Hospital Roberto Gilbert Elizalde of the Board of charities of Guayaquil, indicates that kidney disease are very common, and are a average of 15 patients daily with 5 to 6 consultations of patients in hospital in Nephrology. Presents a study describing the clinical features and the process of care nursing executed, in a case of nephrotic syndrome with infant. The results will allow to develop a valid plan of nursing care for the management of patients with pathology. OVERALL OBJECTIVE Describe the clinical features of the nephrotic syndrome in the nursing major served in the General Hospital of Teofilo Davila of Machala in 2017. METHODOLOGY Developed a qualitative research of descriptive, to apply the heuristic, clinical, analytical, synthetic method based on the analysis unit, s and use techniques such as: literature review, document review of the clinical history of the patient, instruments such as: structured categories tab, guides of non-structured interviews to a specialist in Nephrology and Atty.. Head of Pediatric of a case of nephrotic syndrome served in the General Teofilo Davila Hospital during the period November to December 2017. RESULTS: Nephrotic syndrome is a rare disease at global, national and local level, the age of presentation of nephrotic syndrome in children ranges 2 to 10 years of age, as a syndrome of minimal change nephrotic, and less than a year as nephrotic syndrome congenital; our unit of analysis by the age of presentation and the absence of pathological prenatal and post-natal antecedents, nor pathological families, allows us to associate it with the type of idiopathic nephrotic syndrome, without ruling out the possibility of being of type. The clinical features of the nephrotic syndrome in greater infant are, bilateral palpebral edema and upper and lower limbs, coughing without expectoration of moderate intensity, diarrheal stools, with results of proteinuria, dilucional, hyponatremia, severe hypoalbuminemia, hypertriglyceridemia and hypercholesterolemia, nursing care performed revelor weaknesses in the assessment and response to the needs of the patient. CONCLUSIONS In relation to the results, the clinical characteristics of the nephrotic syndrome, the key piece to carry out a process of attention to the disease, the same one that is based on the diagnostic approach with the NANDA taxonomy, where the altered domains were identified, was handled the corresponding NIC and NOC, which has its use and applicability in the field of health.